Development of information technology for supporting the process of adjustment of the food enterprise assortment - Kharkianen, Olena; Myakshylo, Olena; Hrybkov, Serhii; Kostikov, Mykola (Eastern-European Journal of Enterprise Technologies, 2018)
The work aims to study the processes of production management at the multiproduct food enterprises. To improve management effectiveness, application of the created information technology to support the process of adjusting the product assortment was proposed. This is achieved by reducing the total product cost price and obtaining an additional profit. The proposed information technology consists of five main stages which provide a deep analysis of production based on the accumulated business information about the company's activities, sales, market demand, quality and quantity indicators of the products, formulations, etc. The stages of the developed information technology include application of the data mining methods such as clustering, decision trees, forecast methods based on time series. Each proposed method of data mining was substantiated and tested for each of the stages of the proposed information technology. The essential feature of the proposed technology is that adoption of the forecast level of cost price and demand are estimated using graphical and analytical methods of break-even calculation. The use of this technology will improve efficiency of economic activity of enterprises. This is achieved by reducing the product cost price. The proposed technology can be used both in the food industry and in other similar industries.